Measurements and modeling of PAH soot precursors in coflow ethylene/air laminar diffusion flames. (15th January 2019) - Jerez, A.; Cruz Villanueva, J.J.; Figueira da Silva, L.F.; Demarco, R.; Fuentes, A.
Abstract: New experimental and numerical results of a laminar ethylene-air co-flow non-premixed flame are compared, in terms of soot volume fraction and temperature, and of polycyclic aromatic hydrocarbons (PAH) distributions. Measurements involved UV-excited laser induced incandescence (properly calibrated), planar laser induced fluorescence (PLIF), and deconvoluted two-color pyrometry. In order to evidence soot and PAH, the comparison of prompt and delayed detection is carried out at four spectral detection wavelengths (340, 400, 450 and 550 nm). Numerical results are obtained using a detailed gas-phase chemical kinetics mechanism considering 94 species and 719 reactions, and a sectional soot model, together with a statistical narrow band correlated K (SNBCK) wide band model to account for radiation. Computed PAH, grouped by their number of rings, is found to exhibit a good correlation with experimental PLIF results at different spectral detection wavelengths. In particular, it is shown that 340 and 400 nm fluorescence signals indicate the presence of one up to four-ringed computed PAH, whereas the interpretation of measurements at larger wavelengths is found to be elusive, due to soot signal overlap. Furthermore, an interplay between temperature decrease, soot volume fraction increase and radiative heat transfer distribution with increasing fuel flow rate is also demonstrated.